Effects of post-teneral nutrition and ginger root oil exposure on longevity and mortality in bait treatments of sterile male Ceratitis capitata - San-Andrés, Victoria; Pérez-Panadés, J.; Carbonell, Emilio A.; Castanera, Pedro; Urbaneja, Alberto (2017)
Area-wide Sterile Insect Technique (SIT) programmes against medfly, Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), are being increasingly implemented worldwide. A key issue for SIT is to release sterile males that are sufficiently competitive with males from the wild population. Post-teneral nutrition and ginger root oil (GRO) exposure of sterile males prior to release have been shown to improve male competitiveness or performance. However, few studies are available on the effect of post-teneral nutrition and ginger oil exposure on longevity and mortality in bait treatments by sterile male C. capitata. In this study, we found that longevity was increased by the addition of protein to the standard pre-release sugar diet, whereas exposure to GRO did not influence the longevity of sterile males. Mortality in spinosad baits was influenced both by diet and GRO exposure. Sterile males on a protein-deprived diet suffered greater mortality than sterile males fed with both sugar and protein. When sterile males were fed on the protein-deprived diet, GRO exposure increased their mortality. However, no significant differences were found in adults on the sugar-protein diet, whether or not they had been exposed to GRO. These results show, for the first time, a negative effect of GRO exposure in terms of increasing mortality in proteinaceous bait treatments, a common practice in areas where SIT is implemented. Nevertheless, this effect could be reduced by the addition of protein to the standard pre-release diet. The implications of these results for SIT programmes against C. capitata are discussed. © 2009 The Netherlands Entomological Society.